2017
DOI: 10.5575/geosoc.2017.0059
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in lower crustal process:

Abstract: Ultrahigh-temperature (UHT) and ultrahigh-pressure metamorphism indicate extreme metamorphic conditions in regional metamorphic settings. In particular, the metamorphic temperature of UHT metamorphism is the highest limit of crustal metamorphism, exceeding °C and is equivalent to the temperature of basaltic magma. Typical UHT metamorphic rocks have Mg-Al-rich bulk chemical compositions and are easily identified by a characteristic mineral assemblage of sapphirine + quartz garnet, orthopyroxene + sillimanite qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 191 publications
(62 reference statements)
2
2
0
Order By: Relevance
“…3b, 3d, and 3g). These distinct ages from detrital Zrns might indicate metamorphism timing, which is quite consistent with previous reports (Sakashima et al, 2003;Takagi and Arai, 2003;Dunkley et al, 2008;Maki et al, 2014;Osanai et al, 2017;Suga et al, 2017).…”
Section: Interpretation Of Zrn U-pb Agessupporting
confidence: 93%
See 2 more Smart Citations
“…3b, 3d, and 3g). These distinct ages from detrital Zrns might indicate metamorphism timing, which is quite consistent with previous reports (Sakashima et al, 2003;Takagi and Arai, 2003;Dunkley et al, 2008;Maki et al, 2014;Osanai et al, 2017;Suga et al, 2017).…”
Section: Interpretation Of Zrn U-pb Agessupporting
confidence: 93%
“…The subsequent retrograde stage promoted new Zrn crystallization from melts and Grt breakdown at~110 Ma, finally involving granitic intrusion into pelitic gneisses at~105 Ma. Although the timing of the HT metamorphism in the Higo metamorphic terrane (~110-120 Ma) is consistent with that of previous studies (e.g., Sakashima et al, 2003;Takagi and Arai, 2003;Dunkley et al, 2008;Maki et al, 2014;Osanai et al, 2017;Suga et al, 2017), this study reconfirmed the rapid HT metamorphism framework from detailed observation of Zrn internal textures, REE chemistry, and U-Pb ages, providing critical information to understand the tectonic evolution of this terrane.…”
Section: Interpretation Of Zrn U-pb Agessupporting
confidence: 89%
See 1 more Smart Citation
“…F I G U R E 1 1 CL image of studied metagabbro (SGN-Gb1914) of Sambagawa metamorphic rocks. Each LA-ICP-MS-analyzed spot is labeled with the concordant 206 Pb/ 238 U age with 2σ error and the Th/U ratio Furthermore, Osanai et al (2017) reported that zircon in garnet-cordierite-biotite gneiss and cordierite-biotite tonalite displays the dark CL image and has weak oscillatory zoning. These features are also almost consistent with our result of the internal texture of zircon grains in tonalite samples from "Sashu mylonite" (Figure 8d,e).…”
Section: Zircon U-pb Age Of Sambagawa Metamorphic Rocks North Of "Smentioning
confidence: 99%